EDWARD M. CORRADO and HEATHER LEA MOULAISON, Digital Preservation for Libraries, Archives, & Museums - Force, Donald C. (Archivaria, 2015)
Digital Preservation for Libraries, Archives, & Museums. EDWARD M. CORRADO and HEATHER LEA MOULAISON. Lanham, MD: Rowman & Littlefield, 2014. xxiii, 270 pp. ISBN 978-0-8108-8712-1.